The ecology and evolution of individual behavioural variation - De Winter, Gunnar (2017)
Central to this thesis is the investigation of how several factors (e.g. morphology, ecology, and social conditions) co-vary with consistent individual behavioural variation. Additionally, conceptual work explores the reach of consistent inter-individual behavioural variation in several novel contexts. In doing so, the aim is to contribute novel findings to the quickly growing compendium of knowledge concerning 'animal personality' in various settings. In summary, during this PhD the following research has been performed: • Through the use of lab-reared juvenile three-spined stickleback (Gasterosteus aculeatus) whose parents came from different habitats, I investigated the relative contribution of plasticity and (epi)genetic mechanisms on three behaviours (boldness, activity, and sociality). While these behaviours did not differ between juveniles from both populations, correlations of body length with specific behaviours did. (Chapter 2) • During fieldwork on the Scottish island of North Uist, seven populations of wild three-spined stickleback were surveyed for boldness, exploratory behaviour, and activity. Furthermore, the defensive morphology of these fish was quantified following an armour-staining protocol. Bold fish were found to be less armoured, directly contradicting the phenotypic compensation hypothesis, while more active fish were more armoured, which contradicts the idea that armour is energetically costly. (Chapter 3) • Spurred on by the findings on morphology-behaviour correlations, the ecology of the studied populations was assessed with a focus on parasitism by three common macro-parasites of three-spined stickleback, predation by trout, competition with the nine-spined stickleback, and the availability of resources. I found that all these factors, to some extent, influence individual behavioural variation. Importantly, this study provides the first observational evidence that less-explored factors, such as resource availability and interspecific competition, can be highly relevant influences on individual behaviour. (Chapter 4) • Next, a study on the effect of group behavioural composition on group foraging behaviour was done. With the help of a research visit to Aarhus University, similar experiments were performed on stickleback and social spiders (Stegodyphus dumicola). Group behavioural composition had a strong effect in both study systems, but experience was a more relevant influence on group foraging behaviour in stickleback. By using two different study organisms from quite disparate animal taxa, this allows me to develop hypotheses concerning the evolutionary origin and maintenance of individual behavioural variation and its tentative link with sociality. (Chapter 5) • Lastly, the phenomenon of consistent individual variation in behaviour is explored in novel contexts through conceptual essays (Chapter 6). o Do bacteria offer a suitable system to study ‘personality’? o How can animal personality be leveraged to improve animal welfare? o Are non-antagonistic interspecific interactions an overlooked yet important factor in the study of animal personality?